Mapping and Validating a Point Neuron Model on Intel's Neuromorphic Hardware Loihi - Dey, Srijanie; Dimitrov, Alexander (Frontiers in Neuroinformatics, 2022)
Neuromorphic hardware is based on emulating the natural biological structure of the brain. Since its computational model is similar to standard neural models, it could serve as a computational accelerator for research projects in the field of neuroscience and artificial intelligence, including biomedical applications. However, in order to exploit this new generation of computer chips, we ought to perform rigorous simulation and consequent validation of neuromorphic models against their conventional implementations. In this work, we lay out the numeric groundwork to enable a comparison between neuromorphic and conventional platforms. ‘Loihi’ - Intel's fifth generation neuromorphic chip, which is based on the idea of Spiking Neural Networks (SNNs) emulating the activity of neurons in the brain, serves as our neuromorphic platform. The work here focuses on Leaky Integrate and Fire (LIF) models based on neurons in the mouse primary visual cortex and matched to a rich data set of anatomical, physiological and behavioral constraints. Simulations on classical hardware serve as the validation platform for the neuromorphic implementation. We find that Loihi replicates classical simulations with high precision and very efficiently. As a by-product, we also investigate Loihi’s potential in terms of scalability and performance and find that it scales notably well in terms of run-time performance as the simulated networks become larger.